1982
DOI: 10.1159/000249938
|View full text |Cite
|
Sign up to set email alerts
|

Dermal Vasculitis due to Coumadin Hypersensitivity

Abstract: A 65-year-old patient developed nonpruritic purpuric skin eruptions following 10 days of coumadin treatment. Skin biopsy revealed vasculitis and immunofluorescent studies demonstrated the presence of IgM and C3 deposits in the walls of the affected blood vessels. Rechallenge with coumadin was followed by reappearance of the skin eruptions. Indirect mast cell degranulation test and migration inhibiting factor test were positive in the presence of coumadin. These findings strongly suggest that the skin lesions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Also the use of contrast medium may result in allergic reactions, but to the best of our knowledge, these reactions are not of the delayed type. Dermal vasculitis due to coumarin has also been reported [8], But our patient showed a transient clinical picture despite continua tion of oral anticoagulant therapy. The mechanisms of serum sickness have been extensively outlined in the literature [9].…”
Section: Discussionsupporting
confidence: 53%
“…Also the use of contrast medium may result in allergic reactions, but to the best of our knowledge, these reactions are not of the delayed type. Dermal vasculitis due to coumarin has also been reported [8], But our patient showed a transient clinical picture despite continua tion of oral anticoagulant therapy. The mechanisms of serum sickness have been extensively outlined in the literature [9].…”
Section: Discussionsupporting
confidence: 53%
“…Ten reports were identified in the English-language literature from the years 1980 to 2011 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12). From the reports we collected the following data: patient age at onset, cutaneous manifestations, latency (from initiation of treatment to onset of skin manifestations), treatment strategies for vasculitis, concomitant medications, and outcome.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A comprehensive review of existing literature revealed twenty-three cases of anticoagulant-induced LCV, including two attributed to rivaroxaban use (Table 1), [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. It is worth noting that along with our patient, one of the two reported patients with rivaroxabaninduced LCV was prescribed metformin, another drug rarely implicated as a cause of LCV, prior to the development of symptoms [26,28].…”
Section: Case Discussionmentioning
confidence: 99%